Sistematização da assistência de enfermagem na perspectiva para a autonomia profissional - Eric Benchimol Ferreira; Milca Severino Pereira; Adenicia Custódia Silva e Souza; Carlos Cristiano Oliveira de Faria Almeida; Alexandre Chater Taleb (Universidade Federal do Ceará, 2016)
Objective: to analyze the perception of nurses about the systematization of nursing care in the perspective of professional autonomy. Methods: a descriptive and exploratory research, carried out with 24 nurses at five inpatient clinics of a large-scale public teaching hospital, through a structured questionnaire evaluated by experts. Data were analyzed using descriptive statistics. Results: nurses claimed that the systematization of nursing care promotes autonomy, emphasizing that the pursuit of knowledge for the development of systematization of nursing care is supported by an exchange of experiences among colleagues. Conclusion: applying the systematization of nursing care generates autonomy, demonstrating that nurses become more apt in developing it, thereby resulting in increased professional autonomy.